Phylogeny of Holocacista capensis (Lepidoptera: Heliozelidae) from Vineyards and Natural Forests in South Africa Inferred from Mitochondrial and Nuclear Genes - Steyn, L.A.I.; Karsten, M.; Malan, A.P.; Wang, H.-L.; Addison, P. (South African Journal of Enology and Viticulture, 2023)
In South Africa, the family Heliozelidae in the order Lepidoptera is restricted to four known species. The grapevine leaf miner, Holocacista capensis, feeds between the epidermal layers of a grapevine leaf, predominantly along the leaf margin. A final instar larva will descend from the blotch mine/gallery to attach its cocoon casing (constructed from the epidermal layers of the mined gallery) to any object below the infested leaf. Five monophyletic clades and a polyphyletic group have been identified within the Heliozelidae, using a mitochondrially encoded gene cytochrome c oxidase I (COI) and a nuclear gene, histone 3 (H3). An exploratory study of the genetic diversity within H. capensis populations was conducted using these genes. The phylogenetic analyses of COI indicate that H. capensis that are currently being collected from South Africa fall within three clades/haplotypes, of which one is well supported and contains only one species from Gauteng, and one has three specimens from two different areas in the Western Cape province, while 80% belong to haplotype 1 (H1). The current study can be used as a starting point for future DNA-based studies aimed at gaining insight into possible patterns of diversity in H. capensis to confirm switching from native to commercial grapevine hosts. However, more samples need to be collected from different areas in South Africa.